Discrimination and intimate partner violence among a sample of bisexual and gay men in the United States: a cross-sectional study - Rustagi, Khyati; JadKarim, Luzan; Birk, Nick; Tran, Alvin (Frontiers in Public Health, 2023)
Purpose Intimate partner violence (IPV) is becoming more recognized as a public health concern among sexual minority men, including bisexual and gay men. Guided by the Minority Stress Model, we assessed the relationship between perceived discrimination and three forms of IPV among a sample of bisexual and gay men living in the United States. Methods We analyzed data as part of the Men’s Body Project, a cross-sectional study launched in 2020 to assess health behaviors of bisexual and gay men. Results A total of 549 individuals participated in the survey, of which 52% were gay and 48% were bisexual men. Perceived discrimination was significantly associated with elevated odds ratios ranging from 1.15 to 1.18 across three forms of IPV, with Physical IPV odds ratio being highest. Conclusion Given the significant association between perceived discrimination and IPV, interventions aimed at addressing IPV experiences among sexual minority men must consider the role of minority stress.